(untitled) (Teología, 2016)
This text of Gonzalo Zarazaga is the response that he had to the panel that the Society of Theology of Argentina organized in Congress for the Centenary of the Faculty of Theology. From the relationship between faith and testimony, Cecilia Avenatti, Luis Liberti and Gerardo Söding, proposed theological, pastoral and aesthetic keys to meet the challenges of the proclamation of the Gospel in our cultural scene.